Нові знахідки Sphaerotheca savulescui Sandu на сході України - Гелюта, В.П. (Промышленная ботаника, 2004)
New information is provided about distribution of a comparatively rare powdery mildew fungus Sphaerotheca savulescui Sandu (Erysiphales), in the eastern part of Ukraine. It is concluded that this parasite of Adonis L. species is rather common in the southern part of Ukraine, and thus it can be found in adjacent regions of Russia and Moldova.